On the exciton-assisted radiative recombination via impurity trap levels in AlGaN deep ultraviolet light-emitting diodes. (25th June 2021) - Chen, Huashan; Zhao, Zijun; Lin, Yue; Zhu, Lihong; Ma, En; Guo, Weijie; Wu, Tingzhu; Lin, Fulin; Lu, Yijun; Chen, Zhong; Shih, TienMo; Lei, Yuanchao; et al.
Abstract: For decades, problems of parasitic emissions have been ubiquitously encountered in nearly all deep ultraviolet light-emitting diodes (DUV-LEDs). In this work, 450 nm parasitic peaks in 275 nm AlGaN DUV-LEDs have been studied in details. Upon careful comparisons and analyses on the electroluminescence and photoluminescence spectra at various injection levels and different temperatures, we have discovered a mechanism of exciton-assisted radiative recombination, namely, the reinforcement on radiative recombination via other impurity-trap levels (ITLs) by excitons that are generated in the midst of the band gap. For DUV-LED samples under investigation herein, a system of radiative ITLs within the band gap cannot be neglected. It includes two types of impurities located at two different energy levels, 3.80 eV and 2.75 eV, respectively. The former, establishing a sub-band edge, which behaves like an energy entrance to this system, contains a series of hydrogen-like excitons at a temperature lower than 100 K, which behaves like an energy entrance to this system. On the one hand, these excitons absorb carriers from band-edge and reduce the band-edge recombination. On the other hand they transfer the energy to lower impurity levels, enhancing the radiative recombination and giving rise to the 450 nm parasitic peak.